Effects of urbanisation on the parasitoid community of a leafminer - Fenoglio, Maria Silvina (2009)
Urbanisation may have detrimental effects on communities of parasitoids, affecting their species richness, abundance, and species dominance. Here we investigated the influence of the degree of urbanisation on parasitoid communities of Liriomyza commelinae (Diptera: Agromyzidae), a leafminer of Commelina erecta (Commelinaceae), in the city of Córdoba, Argentina. To study changes in species richness, the specific composition of parasitic complexes and their degree of impact on the leafminer, 18 sampling sites from the centre to the outskirts of the city were selected and different variables indicative of urbanisation were quantified in each site. During January and February of 2005 and 2006, all mined leaves found in each plant patch were collected and the following variables were estimated: proportion of mined patches, abundance of the leafminer, total parasitoid species richness, total parasitism rates and parasitism due to the most abundant parasitoid species. The percentage of mined patches and leafminer abundance increased with urbanisation degree. Estimates of parasitoid species richness were not influenced by urbanisation degree but increased with species richness of mined plants. Changes in the specific composition of species along the urbanisation gradient were observed. Although parasitism by one of the species studied was higher in more urbanised sites of the city, the total parasitism rate of L. commelinae was not affected by urbanisation degree, species richness of mined plants or leafminer abundance. It appears that urbanisation benefits the herbivore species here studied but not through altering parasitoid activity. Changes in parasitoid community composition reflex dissimilar tolerance to environmental conditions displayed by different parasitoid species.